ANALYSIS OF OCCUPATIONAL ACCIDENT AND HEALTH RISK CONTROL OPPORTUNITIES IN EAST KALIMANTAN HEAVY EQUIPMENT COMPANIES - Made Yenny Puspitarini; Abdul Rohim Tualeka; Sahrir Sillehu; Ketut Ima Ismara; Nur Aini; Yustinus Denny Ardyanto Wahyudiono (Journal of Vocational Health Studies, 2026)
Background: Mechanical failure, age and poor quality of machines, and heavy equipment can cause mining accidents or disasters. Accidents in mining can be caused by equipment and handling of heavy loads, mechanical failure, safety management, poor leadership and work environment, unsafe actions, inexperienced workers, and lack of rules, regulations, training and safety education. Purpose: The purpose of this study was to analyse risk opportunities for enhancing heavy equipment employee protection performance. Method: This study used a qualitative method, by using Hazard Identification, Risk Assessment, and Risk Opportunities (HIRARO) methods to identify work hazards in mining areas and opportunities to control them to improve safety performance. Result: The risk management that has been carried out by the company does not use a hierarchy of controls, but goes directly to preventive measures with moderate status. Conclusion: Risk management in East Kalimantan heavy equipment companies still needs to be improved in terms of preventing accidents and occupational health by adding risk level after initial controls, to obtain post-initial control risk levels, as well as proper additional controls and take into account the opportunities to enhance OSH performance or reduce risks.